ATG7 and ATG9A loss-of-function variants trigger autophagy impairment and ovarian failure (2019)
Purpose: Primary ovarian insufficiency (POI) is a frequent disorder that affects ~1% of women under 40 years of age. POI, which is characterized by the premature depletion of ovarian follicles and elevated plasma levels of follicle-stimulating hormone (FSH), leads to infertility. Although various etiological factors have been described, including chromosomal abnormalities and gene variants, most cases remain idiopathic. The aim of the present study was to identify and validate functionally new sequence variants in ATG (autophagy-related genes) leading to POI. Methods: We have reanalyzed, in silico, the exome sequencing data from a previously reported work performed in 69 unrelated POI women. Functional experiments using a classical hallmark of autophagy, the microtubule-associated protein 1 light chain 3? (LC3), were then used to link these genes to this lysosomal degradation pathway. Results: We venture a functional link between ATG7 and ATG9A variants and POI. We demonstrated that variant ATG7 and ATG9A led to a decrease in autophagosome biosynthesis and consequently to an impairment of autophagy, a key biological process implicated in the preservation of the primordial follicles forming the ovarian reserve. Conclusion: Our results unveil that impaired autophagy is a novel pathophysiological mechanism involved in human POI. © 2018, American College of Medical Genetics and Genomics.